A decade of gastrocnemius injuries in elite men`s Australian Football: a descriptive epidemiological evaluation - Gray, C.; Pizzari, T.; Schache, A.; Murphy, M.; Green, B. (Journal of Science and Medicine in Sport, 2024)
Introduction: Calf muscle strain injuries are prevalent in elite athletes and recreational sportspeople. Of these, soleus injuries have been a recent focus. Despite this, gastrocnemius injuries remain a cause of time loss and recurrence in a range of sports, including Australian Football. The primary aim of this study is to describe the epidemiology of gastrocnemius injuries in elite Australian football players, focusing on: i) injury type (index vs recurrent); ii) anatomical location (medial head vs lateral head); iii) mechanism of injury; and, iv) player demographics. Methods: Gastrocnemius injuries from ten consecutive seasons (2014-23) reported to the Soft Tissue injury Registry of the AFL (STRAFL) were evaluated. Club medical staff reported injury data for each season, which included: intrinsic player details, previous injury history, mechanism of injury, game and training indices and time to reach recovery milestones (pain free walking, run at >90% of maximum speed, return to full training, return to play (RTP)). Descriptive statistics are presented as Mean±SD and between group differences assessed using Mann-Whitney U-tests with significance set at p<0.05. Results: 101 gastrocnemius injuries in 89 players participating in the elite men`s competition were reported to the STRAFL (~10 per season). Eighty-six (85.1%) were index and 15 (14.9%) were recurrent. The medial head (76.2%) was more commonly injured than the lateral head (23.8%). While some gastrocnemius injuries occurred when accelerating (17.5%), 1-in-2 (50%) lacked a specific inciting mechanism. Recurrences affected older (+2.6 years, p=0.038), more experienced (career games: +84 games, p=0.008; AFL career length: +3.2 years, p=0.023) players. After injury, players took 3.8±3.3 days to walk without pain, 16.7±11.7 days to run at >90% of max speed, 19.9±11.7 days to return to full training, and 24.2±19.1 days to RTP. Gastrocnemius injuries that occurred from a running-related mechanism took significantly longer to RTP than injuries of gradual or nil-specific onset (+13.7 days, p=0.041). Differences in the RTP time frames for recurrent compared to index injuries (30.9±22.4 days vs 23±18.4 days), and lateral compared to medial head injuries (26.3±21.9 vs 23.7±18.4), did not reach significance (p>0.05). Recurrences mostly involved the medial head (93.3%) and occurred within 6 months (86.7%) of the index injury (median: 83 days). Discussion: Gastrocnemius injuries are relatively common in elite Australian Football. While some gastrocnemius injuries occur during mechanisms typically associated with this type of calf muscle strain (e.g. acceleration), our research demonstrated that many gastrocnemius injuries occur without a specific inciting event. Consistent with previous research, medial head injuries are more prevalent than lateral head injuries. We also found medial head injuries represent almost all recurrences in elite Australian Football players. Gastrocnemius injuries that occurred from a discrete inciting running activity were associated with a worse RTP prognosis, consistent with what we have previously found for soleus injuries. Older, more experienced players may be susceptible to recurrence. Impact/Application to the field: When assessing gastrocnemius injuries, clinicians can also use information about the injured athlete, injury onset, and anatomical location to better understand time to RTP and likelihood for recurrence. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.